Hilary Putnam - Ben-Menahem, Yemima, 1946- (Cambridge ; New York : Cambridge University Press, 2005)
The essays in this volume discuss Putnam's major philosophical contributions to the theory of meaning, the philosophy of mind, the philosophy of science and mathematics, and moral theory. The volume also constitutes a critical introduction to a number of central issues in contemporary philosophy.
Putnam's "The meaning of 'meaning'" : externalism in historical context / Juliet Floyd -- The face of perception / Charles Travis -- Realism, beyond miracles / Axel Mueller, Arthur Fine -- Putnam on skepticism / Yemima Ben-Menahem -- The tale of quantum logic / Tim Maudlin -- Another philosopher looks at quantum mechanics, or what quantum theory is not / Nancy Cartwright -- Structural realism and contextual individuality / John Stachel -- The rise and fall of computational functionalism / Oron Shagrir -- The pragmatic turn : the entanglement of fact and value / Richard J. Bernstein.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Putnam, Hilary; Putnam, Hilary; Putnam, Hilary -- 1926-2016; PHILOSOPHY -- History & Surveys -- Modern; Electronic books; Electronic books